The case of the unfamiliar implement: schema-based over-riding of semantic knowledge from objects in everyday action. - Bickerton, W; Humphreys, G; Riddoch, M (2007)
We examined the role of schema knowledge in everyday action by assessing the use of unfamiliar implements by patients with subcortical and frontal lobe damage. Although the patients were relatively good at naming or showing how the unfamiliar implements could be used outside of the task context, the patients omitted using the objects in everyday life tasks more often than control participants--either omitting the action step involving the objects or performing the action using a familiar object that was not normally used for this purpose. The data suggest that knowledge about objects in the context of a task can play a determining role in how objects are used in everyday action. In patients with reduced attentional resources, the task schema can over-ride weak bottom-up cueing of action from the objects, with the result that unfamiliar implements are not used.